2009
DOI: 10.1038/nature08105
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of a widely tunable bandgap in bilayer graphene

Abstract: The electronic bandgap is an intrinsic property of semiconductors and insulators that largely determines their transport and optical properties. As such, it has a central role in modern device physics and technology and governs the operation of semiconductor devices such as p-n junctions, transistors, photodiodes and lasers. A tunable bandgap would be highly desirable because it would allow great flexibility in design and optimization of such devices, in particular if it could be tuned by applying a variable e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

96
2,853
13
16

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 3,428 publications
(2,978 citation statements)
references
References 25 publications
96
2,853
13
16
Order By: Relevance
“…These numerical simulation results were in agreement of the published experimental results [133,134]. More information about the properties of monolayer, bilayer and few-layer graphene can be found in Refs [119,135139]. …”
Section: The Structure Of Graphenesupporting
confidence: 89%
See 1 more Smart Citation
“…These numerical simulation results were in agreement of the published experimental results [133,134]. More information about the properties of monolayer, bilayer and few-layer graphene can be found in Refs [119,135139]. …”
Section: The Structure Of Graphenesupporting
confidence: 89%
“…Figure 7(b) shows the four parabolic bands, as the (AB-stacked) bilayer graphene has four atoms in the unit cell. The band structure of bilayer graphene can be tuned by applying an electric field [114,115], providing appropriate substrates [116] or chemical modulations [117,118], which is expected to attract interests in nanoelectronic and nanophotonic applications [119]. From Figure 7(c), the band structure of (ABA-stacked) trilayer graphene seems to be a combination of those of monolayer and (AB-stacked) bilayer.…”
Section: The Structure Of Graphenementioning
confidence: 99%
“…The results showed that fluorinated graphene (fluorination for 5 days) exhibited two emission peaks at approximately 3.80 eV and 3.65 eV indicating wide bandgaps, while no emission was obtained in graphene with zero bandgap. [[qv: 13a]],54 Specifically, the peak at 3.80 eV corresponded to the band‐to‐band recombination of a free electron and a hole, which was found in the bandgap of fluorinated graphene measured by near edge X‐ray absorption spectroscopy (NEXAFS) (Figure 8c). [[qv: 13a]] The peak at 3.65 eV was 156 meV (1260 cm −1 ) below the bandgap because of phonon‐assisted radiative recombination across the bandgap where the C–F vibration mode was excited when the electron‐hole pair recombined.…”
Section: Propertiesmentioning
confidence: 99%
“…Despite these aforementioned superiorities, pristine graphene suffers from several shortcomings including structural defects, chemical inertness and a zero bandgap. Thus, many functionalization methods such as chemical bonding, loading or generating functional groups or free radicals on graphene (or its derivatives) have been utilized to improve structural integrity, surface activity and processability 3. The functionalization not only inherits unique carbon conjugated structures but also brings about a promise to alter the graphene's properties including dispersion, orientation, interaction and electronic properties 4…”
Section: Introductionmentioning
confidence: 99%
“…12 Potentially, graphene-based electronics could consist of just one or a few layers of graphene; however, the absence of a band gap presents a conundrum for the implementation of conventional device architectures, similar to those based on semiconducting materials. [13][14][15][16][17][18] Several methods have been proposed for opening band or transport gaps in graphene, such as patterning single-layer graphene into narrow ribbons, 19 introducing nanoholes into the graphene sheets, 20 applying a perpendicular electric field, [13][14][15][16][17][18][21][22][23][24] or applying mechanical strain. 25,26 Unlike bilayer graphene, gap-opening in trilayer graphene depends on the stacking order of the layers, and notably for ABA (Bernal) stacking it remains metallic even in the presence of a perpendicular electric field.…”
mentioning
confidence: 99%